2010
DOI: 10.1517/14712598.2010.485187
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 receptor blockade with humanized monoclonal antibody for solid organ transplantation

Abstract: Novel applications, such as long-term use in combination with calcineurin-inhibitor dose reduction and its value in the treatment of acute or chronic rejection have yet to be explored. Since daclizumab has been withdrawn from the market, future IL-2 receptor blockade will have to be achieved with basiliximab, which is a chimeric, monoclonal antibody directed against the same epitope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
0
25
0
3
Order By: Relevance
“…Basiliximab is a chimeric antibody, whereas daclizumab is humanized. 41 In a study using data from the Scientific Registry of Transplant Recipients Bustami et al found a significant increased adjusted relative risk for PTLD using basiliximab or daclizumab. 42 However, other registry studies failed to find an association between anti-CD25 induction therapy and risk for PTLD, leading to the general assumption that basiliximab and daclizumab do not increase the risk for PTLD.…”
Section: Monoclonal T Cell Depleting and Non-depleting Antibodiesmentioning
confidence: 99%
“…Basiliximab is a chimeric antibody, whereas daclizumab is humanized. 41 In a study using data from the Scientific Registry of Transplant Recipients Bustami et al found a significant increased adjusted relative risk for PTLD using basiliximab or daclizumab. 42 However, other registry studies failed to find an association between anti-CD25 induction therapy and risk for PTLD, leading to the general assumption that basiliximab and daclizumab do not increase the risk for PTLD.…”
Section: Monoclonal T Cell Depleting and Non-depleting Antibodiesmentioning
confidence: 99%
“…No recent randomised trials comparing ATG with no induction exist. Trials comparing IL-2R antagonists with no induction have shown contradictory results [19,20]. Alemtuzumab was analysed against no induction in a large retrospective study showing a significant reduction in rejection episodes.…”
Section: Induction Therapy -To Do It or Not To Do It?mentioning
confidence: 99%
“…Recently, there has been the introduction of tacrolimus and mycophenolate mofetil in maintenance immunosuppressive therapy. New immunosuppressive drugs are represented by monoclonal antibodies and agents that inhibit proliferative signals [71]. Rituximab is used with great success in AMR treatment.…”
Section: Therapeutic Approaches In Heart Rejectionmentioning
confidence: 99%
“…It is a monoclonal chimeric antibody directed against CD20, previously used to reduce pre-sensitization in heart transplantation candidates [72]. A current approach, in early post heart transplantation, provides the combination therapy with calcineurin inhibitors, anti-proliferative agents and gluco-corticosteroids; maintenance therapy includes the same drug combination but at lower doses [68][69][70][71].…”
Section: Therapeutic Approaches In Heart Rejectionmentioning
confidence: 99%
See 1 more Smart Citation